Exploring pedagogical perspectives of EFL instructors: advantages, disadvantages, and implications of Blackboard as an LMS for language instruction - Saleem Mohd Nasim; Syeda Mujeeba; Shadi Majed AlShraah; Irshad Ahmad Khan; Amir; Zuraina Ali (Cogent Social Sciences, 2024)
The Blackboard learning management system (LMS) is one of the online platforms for teaching a range of subjects. This study explores the perceptions of English as a Foreign Language (EFL) instructors regarding Blackboard for teaching English language skills. It also identifies the advantages and disadvantages of Blackboard compared to face-to-face (F2F) instruction. To collect data, the study employed a convergent/parallel mixed-methods (QUAN-QUAL approach) design. First, a total of 47 instructors from a Saudi university participated in completing a 7-item closed-ended questionnaire. Then, 14 teachers provided feedback through an open-ended questionnaire on the pros and cons of Blackboard versus face-to-face instruction. Data analysis techniques included descriptive statistics and thematic analysis and comparing the results. The findings demonstrate that EFL instructors have mixed responses. They favor Blackboard as an effective medium for teaching listening, reading, speaking, and pronunciation. However, they suggest that writing and grammar skills are taught face-to-face better. This research contributes to understanding Blackboard as an LMS with its pros and cons in EFL teaching and its implications for language instruction to inform decision-making processes.